(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Arbuscular mycorrhizal fungi (AMF), belonging to the phylum Glomeromycota, establish symbiotic associations with plant roots, enhancing nutrient uptake through extensive hyphal networks. These networks facilitate the acquisition of essential nutrients, particularly phosphorus, while the host plants supply the fungi with photosynthates. This review examines the impact of AMF inoculation on onion, tomato, cucumber, and pepper. The findings highlight the numerous benefits conferred by AMF symbiosis, which includes significant enhancements in plant growth and development. AMF inoculation has been shown to improve photosynthetic efficiency, increase plant height, leaf area, root length, and both fresh and dry biomass, as well as boost fruit yield in terms of number, size, and weight. Furthermore, AMF contribute to improved nutrient and water absorption by extending their hyphae into deeper soil layers, thereby enhancing resource availability for plants. Additionally, AMF inoculation plays a crucial role in mitigating biotic and abiotic stresses in vegetable crops while also improving soil stability by reducing leaching and erosion.